Pendidikan Berkarakter dalam Mata Kuliah Bahasa Indonesia di Universitas Serang Raya - Dewi, Lina Marliana (Jurnal Artikula, 2019)
This study aims to determine the character education in Indonesian language courses at the University of Serang Raya, the research method used in this study is a quantitative research method with a descriptive quantitative approach, descriptive research is research conducted to determine the value of independent variables, either one variable or more (a stand-alone variable), without making comparisons or connecting one variable to another. The results of our research have obtained a pretty good data from the students and female students can be concluded that the average student and unsure student are very understanding of character education from character values, character educated ways, the importance of character education instilled early on, have a good understanding of good character education in daily life and lecturers are good motors in motivating students well.